Antibiotic Sensitivity of Bacteria Causing Urinary Tract Infection (Bangladesh Journal of Infectious Diseases, 2017)
Background: Urinary tract infection is very common in both male and female.Objectives: The purpose of the present study was to see the antibiotic sensitivity pattern of isolated from urinary tract infected patients.Methodology: This cross sectional study was carried out in Dhaka Medical College Hospital, Dhaka for a period of 12 months. Clinically diagnosed cases of urinary tract infection irrespective of age and sex having pus cells ?5/HPF in the deposits of centrifuged urine were selected as study population. Data regarding organisms causing UTI and their antibiotic sensitivity patterns were collected. For urine culture the urine samples were inoculated on HiCrome UTI agar, CLED agar, 5% sheep blood agar and MacConkeys agar media with a calibrated loop having diameter of 1.45 mm which contains 0.001 ml of urine. The inoculation at 37o C for 24 hours and CFU count of 105/ml of urine were considered positive for UTI. Identification of bacteria was done by standard biochemical techniques and their distinct colony characteristics. All the isolated organisms were tested for antimicrobial sensitivity against different antimicrobial agents by disc diffusion method on Mueller-Hinton agar plates.Result: Diagnosis of bacteria causing UTI with their sensitivity to different antibiotics was performed with a total of 300 samples from both male (38.66%) and female (61.33%) of different age groups. Among 300 samples 107 strains were isolated. Out of 107 identified strains, 95(31.67%) samples showed single growth and 6(2%) samples showed mixed growth. Escherichia coli (64.49%) was found to be the predominant organism. Regarding antimicrobial sensitivity pattern Esch. coli showed 98.55 to 63.77% sensitivity to imipenem, amikacin, ceftazidime and nitrofurantoin. Other isolated organisms showed 50 to 100% sensitivity to ceftazidime, amikacin, imipenem except Klebsiella, Pseudomonas and enterococci spp. which showed 40% and less sensitivity.Conclusion: In conclusion Escherichia coli is the most commonly isolated bacteria which is highly sensitive to imipenem.Bangladesh J Infect Dis 2015;2(1):13-18